A Frequency Reconfigurable Compact Planar Inverted-F Antenna for Portable Devices - Adnan Ghaffar; Ahsan Altaf; Aayush Aneja; Xue Jun Li; Salahuddin Khan; Mohammad Alibakhshikenari; Francisco Flalcone; Ernesto Limiti (International Journal of Antennas and Propagation)
In this paper, a low-profile, compact size, inexpensive, and easily integrable frequency reconfigurable antenna system is proposed. The proposed antenna consists of an inverted-F shape antenna, capacitors, and switching PIN diodes. The designed antenna element is fabricated on easy available and less expensive FR-4 substrate (εr  = 4.4, tan δ  = 0.02). The switching diodes are incorporated within the radiating structure of the antenna design, and by changing the different states of PIN diodes, frequency reconfigurable response is achieved. While adjusting the different states of the diodes, the antenna resonates between 0.841 GHz and 2.12 GHz and covers six different frequency bands. The proposed system has compact size of 44×14×3.2 mm3. The gain of the antenna is between 1.89 and 2.12 dBi. The measurement results shows the good agreement with simulated results for different key performance parameters. Additionally, the proposed antenna shows omni-directional far-field characteristics for various different frequencies.